Voces de Nueva York: el talante New Yorker y el relato - Burillo Gadea, María Rosa (Revista de Filología Románica, 2009)
The stories published at The New Yorker are at the core of the ideals and thoughts at middleclass America, and the readers identify themselves with their search for certainty, routine and consumption, that they overtly come to associate with a world meant for happiness. They are well-off Americans, and the way of life the stories reproduce reminds society that contemporary times have come out short of adventures. The description of characters as individuals is shown as a matter of conscience distinguishing the right from what is wrong in a further attempt to look for justice. The thing is whether the stories reach the potential subtleties that wise readers may enjoy, or whether conflicts remain typically unsolved reassumed as temporary crises. It is presumed that a reader coming out late from work is far too worn for serious reading. Nonetheless, a careful study proves true the potential extra meaning of the images. This is the subject- matter of the study, its main concern and goal.
Keywords: Editorial policy; Formula; Trespasser; Paralysis; Indulgency